2012
DOI: 10.1021/ef301231a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Lignin Dissolution and Regeneration in Ionic Liquid

Abstract: Density functional theory (DFT), atoms in molecules (AIM) theory, natural bond orbital (NBO) analysis, and Wiberg bond index (WBI) are employed to investigate the mechanism of lignin dissolution and regeneration in 1-allyl-3methylimidazolium chloride (AmimCl). Lignin is modeled with 1-(4-methoxyphenyl)-2-methoxyethanol (LigOH). From the theoretical results, it is observed that AmimCl interacts with LigOH mainly by hydrogen bonds (H bonds), and the interaction of AmimCl with LigOH is stronger than that of LigOH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 60 publications
5
67
0
Order By: Relevance
“…One of the possibly reasons is that our biomass pretreatment process was conducted under high acidity and with relatively high water content. In contrast, lignin dissolution dominated in pure ILs under alkali and neutral conditions with the formation of hydrogen bonds between lignin and ILs although lignin degradation also occurred [43]. Another plausible reason is that the solution pH for lignin precipitation in our process was higher than the reported IL processes (pH 3.0 vs pH 2.0), which leads to reduced lignin precipitation.…”
Section: Lignin Recovery Processmentioning
confidence: 69%
“…One of the possibly reasons is that our biomass pretreatment process was conducted under high acidity and with relatively high water content. In contrast, lignin dissolution dominated in pure ILs under alkali and neutral conditions with the formation of hydrogen bonds between lignin and ILs although lignin degradation also occurred [43]. Another plausible reason is that the solution pH for lignin precipitation in our process was higher than the reported IL processes (pH 3.0 vs pH 2.0), which leads to reduced lignin precipitation.…”
Section: Lignin Recovery Processmentioning
confidence: 69%
“…The system was stirred at 75 °C until it became a solution. When the color of the solution turns brown, lignin is completely dissolved (Ji et al 2012). The solutions were transferred into a glass tube for hydrogel formation under a blanket of nitrogen at 75 °C for 1.5 h without stirring.…”
Section: Preparation Of Lignin Hydrogelsmentioning
confidence: 99%
“…However, there are inconsistent results about the molecular mechanism of the dissolution of lignin in ILs. For example, the Janesko and Wang groups independently modeled interactions of the anion and cation of imidazolium chloride IL with 1‐(4‐methoxyphenyl)‐2‐methoxyethanol, a generally used the model compound of lignin, by performing density functional theory (DFT) calculations. Janesko et al found that the lignin model compound shows significant interactions with imidazolium cation via hydrogen‐bonding and π‐π stacking, proposing the importance of the cation for the dissolution of lignin in ILs.…”
Section: Introductionmentioning
confidence: 99%
“…Janesko et al found that the lignin model compound shows significant interactions with imidazolium cation via hydrogen‐bonding and π‐π stacking, proposing the importance of the cation for the dissolution of lignin in ILs. In contrast, based on the calculated results, Wang et al confirmed that lignin can be dissolved in 1‐allyl‐3‐methylimidazolium chloride ([Amim]Cl). These current results indicate that our knowledge of the dissolution mechanism of lignin in ILs is still relatively rare, and do not highlight the pivotal role of the IL anions and cations.…”
Section: Introductionmentioning
confidence: 99%